Small Business Organization Mechanisms And Directions Of Development In The Republic Of Uzbekistan - Otajanov Umid Abdullaevich (Researchparks Publishing, 2022)
The article presents advanced ideas on the mechanisms of small business organization and development directions in the Republic of Uzbekistan. It was noted that it is the result of special attention paid to the rapid development, stimulation and support of small business entities, which play an increasingly important role in ensuring economic growth, creating new jobs, solving the employment problem, and increasing the income and well-being of the population.